The Safety of Nicorandil Therapy and the Relationship with Treatment Adherence in Patients with Stable Angina Pectoris (According to the NIKEA Observational Study) - Yu. V. Lukina; N. P. Kutishenko; S. Yu. Martsevich (Столичная издательская компания, 2022)
The working group of the NIKEA study: Reznik I.I. (Ekaterinburg), Akulina E.N. (Ekaterinburg), Ezhov A.V. (Izhevsk), Shinkareva S.I. (Izhevsk), Grebnev S.A. (Izhevsk), Skibitsky V.V. (Krasnodar), Kudryashov E.A. (Krasnodar), Fendrikova A.V. (Krasnodar), Skibitsky A.V. (Krasnodar), Matyushin G.V. (Krasnoyarsk), Nemik D.B. (Krasnoyarsk), Pitaev R.R. (Krasnoyarsk), Altaev V.D. (Krasnoyarsk), Samokhvalov E.V. (Krasnoyarsk), Stolbikov Y.Y.. (Krasnoyarsk), Voronina V.P. (Moscow), Lerman O.V. (Moscow), Gaisenok O.V. (Moscow), Dmitrieva N.A. (Moscow), Zagrebelny A.V. (Moscow), Zakharova A.V. (Moscow), Balashov I.S. (Moscow), Leonov A.S. (Moscow), Sladkova T.A. (Moscow), Zelenova T.I. (Moscow), Shestakova G.N. (Moscow), Kolganova E.V. (Moscow), Maksimova M.A. (Moscow), Kuimov A.D. (Novosibirsk), Moskalenko I.V. (Novosibirsk), Shurkevich A.A. (Novosibirsk), Nechaeva G.I. (Omsk), Loginova E.N. (Omsk), Gudilin V.A. (Omsk), Mitroshina T.N. (Orel), Zhuravleva L.L. (Orel), Lobanova G.N. (Orel), Luneva M.M. (Orel), Libis R.A. (Orenburg), Kondratenko V.Yu. (Orenburg), Chesnikova A.I. (Rostov-on-Don), Kalacheva N.M. (Rostov-on-Don), Kolomatskaya O.O. (Rostov-on-Don), Dubishcheva N.F. (Rostov-on-Don), Romadina G.V. (Rostov-on-Don), Chugunova I.B. (Rostov-on-Don), Skarzhinskaya N.S. (Rostov-on-Don), Dobrynina N.V. (Ryazan), Yakushin S.S. (Ryazan), Bulanov A.V. (Ryazan), Trofimova Ya.M. (Ryazan), Nikolaeva A.S. (Ryazan), Sokolova L.A. (St. Petersburg), Savinova E.B. (St. Petersburg), Ievskaya E.V. (St. Petersburg), Vasilyeva L.B. (St. Petersburg), Gomova T.A. (Tula), Zubareva L.A. (Tula), Berberfish L.D. (Tula), Gorina G.I. (Tula), Nadezhkina K.N. (Tula), Yunusova K.N. (Tula), Nikitina V.F. (Tula), Dabizha V.G. (Tula), Renko I.E. (Tula), Soin I.A. (Tula)Aim. To analyze the adverse events (AEs) of nicorandil therapy based on the results of an observational study of NIKEA, to assess the relationship between the occurrence of AEs treatment and adherence to it in patients with stable angina pectoris.Material and methods. The study included 590 people who had nicorandil added to the basic therapy of coronary artery disease (CAD). The followup period averaged 21 months. There were two visits of 1 and 3 months of follow-up (V1 and V3), and after 21 months, by telephone contact (PhC21), it was possible to obtain information about 524 patients (89% response), 509 of whom were alive. Information about the treatment adherence and AEs of nicorandil was collected during V1, V3 and at PhC21.Results. Out of 590 people, 402 (68.1%) patients started treatment with nicorandil. During 21 months of follow-up, 35 AEs were registered in 34 patients. There were no serious AEs associated with taking medications in the study. The most frequent AEs of treatment with nicorandil were hypotension and headache, which led to non-adherence to therapy in 94% and 42% of cases, respectively. The majority of AEs (24 out of 35) occurred during the first three months of nicorandil treatment. Both any AEs of drug therapy and AEs of nicorandil therapy, on average, increase the chance of non-adherence to the recommended treatment by 3 times (p=0.004).Conclusion. The results of the NIKEA study confirmed the good safety of nicorandil in patients with stable angina pectoris, the absence of serious adverse events associated with taking this antianginal drug. The most frequent nicorandil AEs were hypotension and headache. Any AEs of therapy increase the chance of patients' non-adherence by 3 times.